Retos, estrategias y lecciones aprendidas para la implementaciónexitosa de procesos de restauración en el Perú - Sabogal, Cesar (2026)
This article analyzes the main obstacles, strategies, and success factors for implementing forest and landscape restoration processes in Peru, based on a literature review and a structured survey of twenty-four experts with experience across different ecoregions. The results show that restoration efforts have advanced under a consolidated national policy and strategic framework but still face limitations in financing, institutional coordination, technical capacities, and land tenure security. From the systematization of experiences and expert perceptions, five key dimensions emerge for effective implementation: territorial governance, financial sustainability, social participation, capacity building, monitoring and learning. Successful experiences combine sound technical planning, community engagement, and tangible benefits such as improved water regulation and sustainable resource management. The paper proposes measures to strengthen governance, diversify financing sources, enhance regional capacities, and promote restoration as a public policy for sustainable territorial development. Forest landscape restoration is highlighted as a strategic opportunity to integrate biodiversity conservation, production, and climate resilience across multiple planning levels in the country.